Budaya Kerapan Kerbau dalam Mempererat Hubungan Sosial Masyarakat dan Mengembangkan Produktivitas Usaha Bisnis Wisata - Erwin Asidah; Selva Selva; Mala Vinusia (IPM2KPE, 2023)
This study aims to determine the early history of the emergence of buffalo karapan culture in Bree Sapugara Village, Kec. Brang Rea, West Sumbawa Regency and to find out the impact of the buffalo race culture in strengthening social relations in the community, Bree Sagara Village, Kec. Brang Rea, West Sumbawa Regency. The method used is a qualitative method with an ethnographic approach. The data sources in this study were primary data and secondary data sources about the Kerapan Buffalo culture in strengthening community social relations in Bree Sapugara Village, Brang Rea District, West Sumbawa Regency. The results of the study show, a) the early history of the emergence of the Kerapan Buffalo culture in Bree Sapugara Village, Brang Rea District, Sumbawa Regency began during the Dutch colonial era, until now it is still maintained by the people of Sumbawa. The difference between the Dutch colonial era and now lies in the rules of the game at that time did not exist, for those who have large buffaloes and are ready to compete, the speed is what appears, and the arena is even in wet rice fields ready for planting rice, no special arena is made. whereas now the attributes used by the buffalo and the jockeys have paid attention to safety, there are class rules based on the age and the age of the jockeys and spur buffalo are given decorations; b) the cultural impact of buffalo racing in strengthening community social relations in Bree Sapugara Village, Brang Rea District, West Sumbawa Regency, namely as a gathering place, brotherhood, containing a high philosophical meaning for one's social degree or position in the midst of Sumbawa society, a symbol of honor and authority, and efforts to preserve Sumbawa culture, develop tourism as a leading tourism event, business and livestock economy, and people's entertainment. Keywords: Kerapan Buffalo Culture, Community Social Relations